The role of Clinical Pharmacists in the improvement of a pharmacovigilance system: A review of the reported adverse drug reactions during 2004-2010 in Mazandaran Province of Iran. - Ebrahim Salehifar; Shahram Ala; Mina Amini; Elham Azhdari; Farzaneh Mir-Shafa (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: Following establishment of Iranian Adverse Drug Reaction (ADR) Monitoring  Center  in  1997, ADR  committees  were  established  in  all  hospitals  of Mazandaran Province of Iran. Clinical pharmacists from Mazandaran University of Medical Sciences have been involved with these committees since 2007. The aim of this study was to compare the results of the pharmacovigilance system before and after active involvement of clinical pharmacists. Methods:  This  study  included Yellow  Cards  filled out  by  healthcare  providers  inMazandaran Province during 2004-2010. Frequency of Adverse Drug Reactions (ADRs), route of administration, reporters, number of reports in each years and damaged organs were focuses. Statistical analysis was performed by SPSS 16 software. P< 0.05 was considered as significant difference. Results: A total of 793 yellow cards were completed during 2004 - 2010. Only 38 ADRs(4.8%) were related to 2004-2007. Most of the reports generated by Nurses (49.3%) followed by Pharmacists and Physicians (P< 0.001). Forty-one reactions (5.2%) were serious, most related to Ceftriaxone, Desfonac and Vancomycin. Conclusion: Clinical pharmacists' intervention regarding establishing ADR committees in the hospitals improved the output of the pharmacovigilance system, although under- reporting is still a major drawback of spontaneous reporting.